Artificially Enhanced Performing Arts. Experiment on the Creative use of AI in Performing Arts - Andrea Paciotto (Antropologia e Teatro)
This article explores the Artificially Enhanced Performing Arts workshop, which took place in Bologna from January 15 to 19, 2024, as part of a collaboration between the Department of Arts at the University of Bologna and the Seoul Institute of the Arts. The workshop investigated the use of artificial intelligence as a creative tool in the performing arts, with participation from a diverse group of Italian and Korean students. Guided by Professors Andrea Paciotto and Kim JaeMin, the experiment aimed to examine the possibilities and constraints of AI within a collective creative process. Through AI-driven exercises and improvisations, participants collaborated across various cultural, linguistic, and technological boundaries. This article outlines the workshop’s methodology, chronicles the participants' experiences, and analyzes audience feedback, highlighting key takeaways from the experiment.